2016
DOI: 10.1007/s11356-016-8102-2
|View full text |Cite
|
Sign up to set email alerts
|

Low C/N ratio raw textile wastewater reduced labile C and enhanced organic-inorganic N and enzymatic activities in a semiarid alkaline soil

Abstract: Application of raw and treated wastewater for irrigation is an extensive practice for agricultural production in arid and semiarid regions. Raw textile wastewater has been used for cultivation in urban and peri-urban areas in Pakistan without any systematic consideration to soil quality. We conducted a laboratory incubation study to investigate the effects of low C/N ratio raw textile wastewater on soil nitrogen (N) contents, labile carbon (C) as water-soluble C (WSC) contents, and activities of urease and deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 80 publications
2
6
0
Order By: Relevance
“…Soil irrigation with wastewater increases the soil conductivity due to its nutrient content and organic matter and soil salinity [7]. High nitrogen contents of wastewater tend to increase the organic and inorganic nitrogen pool [8]. Similar results have also been stated by Elfanssi et al [9] who reported increase in conductivity, organic matter and N content in soil irrigated with raw wastewater.…”
Section: Introductionsupporting
confidence: 65%
“…Soil irrigation with wastewater increases the soil conductivity due to its nutrient content and organic matter and soil salinity [7]. High nitrogen contents of wastewater tend to increase the organic and inorganic nitrogen pool [8]. Similar results have also been stated by Elfanssi et al [9] who reported increase in conductivity, organic matter and N content in soil irrigated with raw wastewater.…”
Section: Introductionsupporting
confidence: 65%
“…Due to increasing interest in the use of sewage for irrigation and in light of the possible effects of sewage on agricultural soils and crop production, the influence of effluent irrigation on the physical, chemical, and biological properties of soil have been well documented [ 6 , 7 , 8 ]. Previous studies have shown that sewage irrigation is frequently accompanied by increases in macro- and micro-nutrients and heavy metals in the soil [ 9 , 10 , 11 , 12 ] in addition to changes in soil microbial functional diversity and enzymatic activity [ 13 , 14 , 15 ]. Sewage irrigation can also increase the risk of crop and groundwater pollution [ 16 , 17 ] and reduce soil quality [ 18 ] and the infiltration rate [ 8 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Soil analysis showed that the soil pH ranged from 7.3 in tap water, 7.6 in soil irrigated by treated water and 7.9 in soil irrigated by wastewater. Soil pH directly affects the life and growth of plants because it affects the availability of all nutrients in the soil [15]. FAO, [31] these…”
Section: Soil Chemical Analysismentioning
confidence: 99%
“…Mean that the accumulated minerals in soil during the experiment under irrigation with treated water and wastewater. The EC explains the presence of salinity which is the most important indicator regarding to fields irrigated with wastewater [15].…”
Section: Third Trial Wastewatermentioning
confidence: 99%
See 1 more Smart Citation